The historicity of madness and the anti-asylum struggle and deinstitutionalization in Brazil (Research, Society and Development, 2023)
The Fool is not always the one who has a mental disorder, but the one who somehow dared to break the rules of society in some way, or those people who somehow are not accepted for not being in accordance with the pre-established “standards”. defined, as what happened in the Middle Ages, when the Holy Inquisition burned women who dared to stand out like witches at the stake. This work aims to present a historical picture of the emergence of asylums and the anti-asylum struggle, focusing on the former Hospital Colônia, in the city of Barbacena. In Brazil in the 1900s, with the implementation of the Hospital Colônia, in Barbacena, it happened that many people were treated like crazy for not fitting into the social “standards” that were taken by the so-called “Trem de Doidos” to Barbacena and left in the Colony, there they were stripped of their identities, far from their families and homes, faced with cruel and atrocious reality, all that was left for him was to move forward in his role as a madman, in the theater of life. Thus, seeing the years slipping through his hands watching his hiking companion lying on a bed, behind the closed curtains. Just listening to the roars, which come from the electroshock waiting for the arrival, of those who are there, you can only hear the roars behind the aisle and suddenly, there is the silence of pain and tiredness that the electroshock caused by those men in white that seemed like an angel, but that in the end only brought pain, sometimes when waking up the curtain opened and emotion no longer existed because the lobotomy was performed there. And now a soul lies and emotions will never exist. Fortunately, some will see these prisons closed and will have their right to return to society, even if there are fights against it, they will not be able to reopen mental prisons, because mental health is not sold, and mental health is not arrested.